Churchill's secret [videorecording (DVD)] - Garai, Romola, 1982-; Gambon, Michael; Duncan, Lindsay; Smith, Jonathan, 1942- (PBS Distribution, 2016)
It is the summer of 1953 and Nurse Appleyard is rushed to a secret location where she discovers her patient is Winston Churchill, the elderly Prime Minister. Churchill has suffered a stroke and may not last the weekend. As Churchill's wife and family gather at his bedside, long-buried tensions rise to the surface.